Đánh giá khả năng xúc tác của Pd/C* và Pt/C* trong phản ứng hydrodeclo hóa pha lỏng 2,3,7,8-tetrachlorodibenzo-p-dioxin - Hùng, Trần Đức; Thắng, Nguyễn Quan; Hải Nam, Chu Thị; Liên, Nguyễn Hồng (Vietnam Journal of Chemistry, 2016)
In this study, two types of commercial catalysts Pd/C* and Pt/C* with different metal concentrations were investigated for their catalytic activities in the hydrodechlorination (HDC) of 2,3,7,8-p-dioxin-Tetrachlorodibenzo-p- dioxin (2,3,7,8-TCDD) in liquid phase. Products of the reaction were determined by gas chromatography mass spectrometry (GC-MS). The results showed that, Pt was not able to promote the reaction. Meanwhile Pd revealed good catalytic activity with over 99 % of 2,3,7,8-TCDD was dechlorinated. The final product of the process was only DD, an expected chlorine-free hydrocarbon at much lower toxicity compared to the raw material 2,3,7,8-TCDD. Keywords:. 2,3,7,8-Tetrachlorodibenzo-p-dioxin, Hydrodechlorination, Pd/C*, Pt/C*.